COST BENEFIT ANALYSIS OF INSTALLING OF SOLAR AND WIND POWER PLANT USING DIFFERENT PARAMETER - Kumar Kishanpuri, Amit; Sharma, A.K. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, we are discussing about the solar power plant and wind power plant. The electrical power is depend on the ray of sun. These are optimizing output by following the sun across the sky for maximum sunlight. These typically give you about a 15% increase in winter and up to a 35% increase in summer. The panel temperatures are much lower in winter, and then find out the minimum power. And the panel temperatures are higher in summer, and then find out the maximum power.